Lucifer ascending : the occult in folklore and popular culture - Ellis, Bill, 1950- (University Press of Kentucky, 2004)
"The success of J.K. Rowling's Harry Potter series sparked a spirited backlash from America's Christian fundamentalists. Potter may be fiction, these commentators argued, but his occultist practices are dangerous and real - and tempting to impressionable young minds." "This controversy, says Bill Ellis, is only the most recent cases of organized religion's concern that the occult may be corrupting our youth. But Potter fans aren't sacrificing Christianity for the dark arts as some religious leaders fear. The attraction of witchcraft and magic among children is a tradition that is hundreds of years old - and not likely to disappear. In fact, the occult has always functioned to empower people in traditionally less powerful social strata: children, women, lower classes. At a time when most worshippers could not read the Bible or understand a church ceremony, paganism offered spiritual fulfillment. When women could not vote or train for a vocation, witchcraft gave them access to knowledge and medicine." "Witchcraft and magic are still very much a part of Anglo-American culture. In Lucifer Ascending, Ellis looks at modern practices that are universally defined as occult, such as carrying a rabbit's foot for good luck or using a Ouija board to contact the dead as well as more esoteric traditions such as the use of "black bibles." The function of this "vernacular occultism" in society, Ellis argues, is not based on an irrational belief in Satan, nor is witchcraft an underground religion that opposes Christianity. Lucifer Ascending examines the occult not as an alternative to religion but rather as a means for ordinary people to participate directly in the mythic realm."--Jacket